Phraseological units of the Idafa type in the Quran - Nailya Gabdelkhamitovna Mingazova, Vitaly Glebovich Subich,; Al-foadi, Raheem Ali; Rafaelevich Zakirov, Rafis (Opción, 2019)
The study aims to investigate phraseological units of the Idafa type in the Quran and their realization in non- Idafa Germanic and Slavic languages (English and Russian) via comparative qualitative research methods. As a result, the formal Idafa phraseologisms are mostly translated with the English A+Pr+gerund, A+infinitive predicative, Pr+complement, the Russian A+Pr+N predicative groups. In conclusion, connotational Idafa always consists of two nominal components whose first element is expressed by the noun whereas the first component of the formal Idafa is represented either by the noun or adjective.